Tracking system using RFID for hiking activity with IoT technology - Masohor, S. M. A. S.; M Z H A Bakar, M. Z. H. A.; Yamin, W. S. A. W.; Abd Wahab, Mohd Helmy; Ahmad, Muhammad Shukri; Ma’Radzi, Ahmad Alabqari; Tg. Ibrahim, Tg Nadzlin; Chew, Chang Choon (2020)
Hiking is popular in Malaysia because of the geographical factors that have a lots of mountains. Since this is an extreme activity, it gives a lot of risk for the hikers. There were 134 incidents in the mountains reported during 1996 until 2014 where 52 cases are about missing people. When encounter with missing people cases, it is difficult to pinpoint the last location of victim. Therefore, this project aimed to help the rescuer by providing them information of the victim’s last location by creating a tracking system using RFID in order to store data on each checkpoint along the hiking trails in memory card. This system also equipped with wifi which allowed the system send notification using Telegram Apps. The rescuers can extract the data from the memory card from each checkpoint to trace the last location of the victim before reported missing. By having this information, the rescuers will save a lot of time because they can estimate from which area they should start the search and rescue operation.